"Why are you single, baby?" Reasons for being single based on a Brazilian research - Darlane Silva Vieira Andrade; Maria Gabriela Hita (Acta Universitatis Lodziensis: Folia Sociologica, 2021)
Single people are often asked about the reasons for non-marriage, in a context where, despite several changes in the field of intimacy, adults are still expected to marry. Based on a thesis study on the subject of singleness in Brazil, in the city of Salvador, Bahia, this text presents the main reasons for singleness, declared by single middle-class adults who live alone in this city. The study used a feminist perspective, with the category gender as the basis for data analysis, in an intersectional way with social class, race, generation, sexuality and territoriality. It used mixed methods with a combination of instruments: questionnaire, focus groups, biographical interviews, and field observations. The findings collaborate to observe gender differences and closeness in reasons for singleness: relational reasons prevailing for women and being single as a choice for men.